EXPLORING EFFECTS OF INCUBATION ON CREATIVITY, PROBLEM SOLVING AND META-COGNITION - Siddique, Akifa Mariam; R S, Maragatham (PEOPLE: International Journal of Social Sciences, 2018)
The world today is characterized by stiff competition and people develop an urge for being in the top notch of the society. Universally across all age groups - the bosses, teachers and parents are pushing their staff or children to reach the pinnacle point. At these junctures, the caliber of the outcome suffers a quantum decrease because quantity and quick work overpowers quality. The importance of “breather time” also referred as the time period where one lets go of focus on the present task and focuses on subliminal activity is called as Incubation. This can immensely contribute to the quality, quantity as well as efficiency in time.To draw an analogy between the Mad rush and Creative production, it is important to note the ideals of the Psychologist Wallas, 1926 who proposed the term “Incubation”. This downtime has a positive effect on creativity and problem solving (Dodds et al., 2003; Sio and Ormerod, 2009). Meta-cognition is another key cognitive function which enhances planning and learning outcomes, and proves to be a guide for self-monitoring. This research aims to find out the importance of incubation in creativity, problem solving and meta-cognition. The research design was constructed with experimental tests including pre and post-test. The groups were randomly synthesized. The results of the research should prove on how an experiment with a brief time with no activity would fetch good results as compared to continuous work with no assimilation time. This is congruence with a classic proverb “All work with no play makes jack a dull boy”.